Approaches to exchange rate policy : choices for developing and transition economies - IMF Institute; Barth, Richard C.; Wong, Chorng-Huey.; IMF Institute (Washington, D.C. : International Monetary Fund, 1994)
This book is the first published set of proceedings from one of the IMF Institute's seminar.
"Papers presented at the seminar on Exchange rate policies in developing and transition economies, December 3-11, 1992."
Includes bibliographical references.
aug 06/06/13; nmn 24/06/15
Loan
Keywords: Foreign exchange - government policy; Foreign exchange - government policy - europe eastern; Foreign exchange rates - developing countries; Foreign exchange rates - central europe; Foreign exchange rates - europe eastern; Developing countries